Improving Teacher's Competence in Developing Lesson Plan Oriented High Order Thinking Through Mentoring on Social Science Subject in SMP 7 Padang - Iryasman Iryasman; Khairani Khairani (Postgraduate School, Universitas Negeri Padang, 2020)
This research motivated by the need to improve teachers' competence to develop lesson plans oriented towards higher-order thinking skills. The purpose of this research was to obtain the information and discuss in improving teachers' competence to develop lesson plans oriented towards higher-order thinking skills learning through mentoring on social science in SMPNegeri 7 Padang. The type of this research was a school action research conducted for 3 cycles. The method of providing action used is assistance. The subjects of this research were 4 Social Sciences teachers at SMP Negeri 7 Padang. This research was conducted in the even semester of January - June in the 2019/2020 academic year. The research procedure followed the action research cycle of the Kemmis& Taggart model which included planning, action, observation, and reflection (American Journal of Educational Research, 2016). Data collection techniques include documentation, observation, and interviews. Data analysis techniques using descriptive analysis. From the analysis and discussion of the results of the mentoring for 3 cycles, it was concluded that the mentoring activity could improve teacher competence in developing lesson plans based on higher-order thinking oriented learning.